Health Star Ratings and Beverage Purchase Intentions: A Study of Australian and New Zealand Hospitality Consumers - Rob Hallak (MDPI AG, 2021)
This study examines the effects of a health star rating system on the attitudes of consumers and their purchase intentions towards beverage products sold in hospitality venues. Previous studies linking health ratings to the food and beverages of consumers mainly focus on fast-moving consumer goods and retail purchasing. However, purchasing patterns in hospitality and foodservice environments are distinct as consumers may be less concerned about health and more interested in the dining experience. Thus, this research focuses on: (1) whether the presence of health star ratings on beverage products influences the willingness of consumers to purchase in the context of the hospitality industry, and (2) identifying the demographic and psychographic factors influencing these behavioural intentions. Using Ordinary Least Squares regression to analyse data from an e-survey of 1021 consumers in Australia and New Zealand, the study found that health star ratings do have an impact on the willingness of consumers to purchase healthy beverages. Specifically, psychographic segmentation around ‘health goals’ is far more pertinent to understanding purchase behaviour in a hospitality setting than age, gender, income, or country. The findings present new insights into the importance of health star labelling on beverages and the purchase intentions of consumers.